THE ANTHROPOCENTRIC ASPECT OF ENGLISH PHRASEOLOGICAL UNITS - Kholikova Dilfuzakhon Abdumukhtorovna (Bright Mind Publishing, 2025)
This article examines the historical, cultural, and anthropocentric foundations of phraseological units in English and Uzbek. It argues that, as nations and states develop, their languages likewise evolve, acquiring new semantic layers and cultural significance. Phraseological units, being integral components of the lexical system, possess their own historical trajectories, and understanding their origins is essential for their accurate and contextually appropriate use. The study highlights that anthropocentric perspectives—now central in modern linguistics—have long been embedded in the formation and semantic evolution of phraseological units. Through comparative analysis, the article explores how social changes, worldviews, and cultural values shape phraseological meaning, resulting in the aging or transformation of certain idioms. Drawing on the theoretical frameworks of L. P. Smith, V. P. Zhukov, V. N. Teliya, N. M. Shansky, and Sh. Rahmatullaev, the research demonstrates that idioms serve not only as carriers of cultural and historical information but also as powerful pragmatic tools. Special attention is given to the anthropocentric nature of idioms, their evaluative and expressive potential, and their role in enhancing communicative effectiveness across cultures.
Keywords: Anthropocentrism; phraseological units; idioms; semantic evolution; cultural linguistics; evaluative meaning; pragmatics; English; Uzbek; linguistic heritage.